An Exploration of Physics Concepts in Pletokan (Luthang) Traditional Game: What is the Potential of a Physics Learning Media in the Merdeka Belajar Curriculum? - Safitri, Afaurina Indriana; Admoko, Setyo; Suprapto, Nadi; Putri, Rahmah Trinita; Alhusni, Hanan Zaki (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
This research explores physics concepts in depth in pletokan to be integrated into physics learning in the Merdeka Belajar curriculum. Using a qualitative descriptive approach and data triangulation techniques (observation, interviews, and literature study), this research identified pletokan as a superior contextual media for learning physics. Effectively achieve the learning objectives of the Merdeka Belajar curriculum while providing an enjoyable educational experience. The exploration results obtained specifically show that the traditional game of pletokan involves various physics principles such as gravitational potential energy, friction force, work and energy, ideal gas compression, bulk modulus, sound waves, motion dynamics, parabolic motion, and partially elastic collisions. These findings highlight the potential of Pletokan as a promising ethnoscience-based medium for physics learning, which is beneficial in improving student motivation and academic outcomes. Further research is needed to validate advanced applications and their effectiveness in improving student learning outcomes. Embracing ethnoscience in this way enriches students' understanding by including context and preserving the nation's cultural heritage.